New species of Nemoura (Plecoptera: Nemouridae) from China - Li, Weihai; Yang, Ding (Zootaxa, 2008)
Five species of the genus Nemoura from China are described as new to science: Nemoura concava sp. n., Nemoura junhuae sp. n., Nemoura mesospina sp. n., Nemoura stellata sp. n., and Nemoura wangi sp. n. Their relationships with related species are discussed.